LA‐ICP‐MS analysis of rare earth elements in tooth enamel of fossil small mammals (Ust‐Oda section, Fore‐Baikal area, Siberia): paleoenvironmental interpretation. (19th April 2022) - Ivanova, Varvara; Shchetnikov, Alexander; Semeney, Elena; Filinov, Ivan; Simon, Klaus
ABSTRACT: This paper presents the results of a study of rare earth element (REE) fractionation trends in Quaternary mammal remains with the aim to test stratigraphic provenance. The primary aim was to find a solution to the problem of the formation of small mammal disharmonious associations, which is closely connected to the problem of diagnostics of redeposited paleontological material. REE were analyzed from the tooth enamel of small mammal fossils and sediments collected from five stratigraphic units (Ust‐Oda section of Upper Pleistocene terrestrial sediments, Fore‐Baikal area, Siberia). The Ust‐Oda is currently the only known section in the region where a fixed stratigraphic sequence of the Late Pleistocene to Holocene marine isotopic stages (MIS 5–1) occurs. The results for REE signatures of tooth enamel enable us to draw conclusions regarding changes in physical and chemical environmental conditions during diagenesis and afford the possibility of applying geochemical factors signifying REE fractionation to sample classification. This, in turn, allowed us to establish that some small mammal remains found in sediments belonging to the Ust‐Oda section have been redeposited.